2001
DOI: 10.1046/j.1468-2982.2001.00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and Function of the Immune System: A Meta-Analysis of Clinical Literature Published Between 1966 and 1999

Abstract: Mechanisms underlying migraine precipitation are largely unknown. A role of the immune system in migraine precipitation is a matter of debate because of the association of atopic disorders and migraine. Recently, it was demonstrated that migraineurs benefit from eradication of a Helicobacter pylori infection, which substantiates a possible role for (sub-clinical) infections in precipitation of migraine. Since 1966, about 45 clinical investigations have reported on alterations of immune function in migraine pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
95
1
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(105 citation statements)
references
References 116 publications
(155 reference statements)
4
95
1
4
Order By: Relevance
“…Indeed, recent research has focused on the link between pain and inflammation, and increased tumor necrosis factor-alfa levels, activation of mitogen-activated protein kinases, and endothelial dysfunction are among inflammatory mechanisms that appear to be shared by psoriasis and migraine. [6][7][8][9][10][11][12]27 Along this line, tumor necrosis factor-alfa inhibition may inhibit pain signaling in experimental arthritis and ameliorate endothelial dysfunction in those with psoriasis and psoriatic arthritis, suggesting the potential for targeted anti-inflammatory pharmacologic therapy in the treatment of migraine. [28][29][30] Only very few studies have to our knowledge reported on the association between psoriasis and migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent research has focused on the link between pain and inflammation, and increased tumor necrosis factor-alfa levels, activation of mitogen-activated protein kinases, and endothelial dysfunction are among inflammatory mechanisms that appear to be shared by psoriasis and migraine. [6][7][8][9][10][11][12]27 Along this line, tumor necrosis factor-alfa inhibition may inhibit pain signaling in experimental arthritis and ameliorate endothelial dysfunction in those with psoriasis and psoriatic arthritis, suggesting the potential for targeted anti-inflammatory pharmacologic therapy in the treatment of migraine. [28][29][30] Only very few studies have to our knowledge reported on the association between psoriasis and migraine.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-a is able to induce ectopic activity in nociceptive afferent fibers when applied either topically along the nerve or injected subcutaneously [11]. Finally, it has been reported that TNF-a can induce headache and anti-TNF-a antibody can reduce pain in humans [29].…”
Section: Discussionmentioning
confidence: 99%
“…Migraine is a chronic disease which affects approximately 12-18% of the society, can be accompanied by neurologic and systemic symptoms, and is characterised by mild or severe recurring headache attacks [1]. The aetiology and pathophysiology of the migraine 77-amino-acid precursor, with an enzymatic reaction.…”
Section: Introductionmentioning
confidence: 99%